Damage-tolerant composite design principles for aircraft components under fatigue service loading using multi-scale progressive failure analysis. (June 2017) - DorMohammdi, Saber; Godines, Cody; Abdi, Frank; Huang, Dade; Repupilli, Massimiliano; Minnetyan, Levon
Virtual testing has lately gained widespread acceptance among scientists as a simple, accurate, and reproducible method to determine the mechanical properties of heterogeneous microstructures, early in the production process. As a result of the rapid expansion of the use of composites in aerospace design, virtual testing techniques are, in fact, deemed extremely useful to eliminate unnecessary tests and to reduce cost and time associated with generating allowables for lengthy lifing analyses of structures. Leveraging on a limited set of experimental data, a Progressive Failure Analysis can accurately predict the life and safety of a component/assembly, simply tapping on the physics of its micro-/macro- mechanics material properties, manufacturing processes, and service environments. The robust methodology is showcased using blind predictions of fatigue stiffness degradation and residual strength in tension and compression after fatigue compared with test data from Lockheed Martin Aeronautics and Air Force Research Laboratory). The multi-scale progressive failure analysis methodology in the GENOA software considers uncertainties and defects and evaluated the damage and fracture evolution of three IM7-977-3 laminated composite layups at room temperature. The onset and growth of composite damage was predicted and compared with X-ray CT. After blind predictions, recalibrations were performed with knowledge of the test data using the same set of inputs for all layups and simulations. Damage and fracture mechanism evolution/tracking throughout the cyclic loading is achieved by an integrated multi-scale progressive failure analysis extended FEM solution: (a) damage tracking predicts percentage contributing translaminar and interlaminar failure type, initiation, propagation, crack growth path, and observed shift in failure modes, and (b) fracture mechanics (VCCT, DCZM) predicts crack growth (Crack Tip Energy Release Rate vs. Crack Length), and delamination. The predictive methodology is verified using a building block validation strategy that uses: (a) composite material characterization and qualification (MCQ) software, and (b) the GENOA multi-scale progressive failure analysis fatigue life, stiffness degradation, and post-fatigue strength predictions for open-hole specimens under tension/compression at RTD. The unidirectional tension, compression, and in-plane shear lamina properties supplied by Lockheed Martin Aeronautics and the Air Force Research Laboratory (based on the D3039, D638, D3518 tests) were used by MCQ to reverse engineer effective fiber and matrix static and fatigue properties for the IM7-977-3 material system. The use of constituent properties identified the root cause problem for composite failure and enabled the detection of damage at the micro-scale of the material where damage is incepted. For all three case studies (namely, layups [0/45/90/−45]2s, [+60, 0, −60]3s, and [+30, +60, 90, −60, −30]2s ), the blind predictions on the fatigue stiffness degradation and residual strength of the open-hole coupon in tension/compression under cyclic loading (with R = 0.1) at RTD were evaluated using a FE mesh (made of 2k shell elements), in which only one shell element, containing all plies, was employed through the thickness. The results of all analyses correlated very well with the tests, including the damage micro-graphs generated during the cyclic loading.